Evaluation of In Vitro Synergistic Effects of Tetracycline with Alkaloid-Related Compounds against Diarrhoeic Bacteria - Osei-Owusu, Hayford; Rondevaldova, Johana; Houdkova, Marketa; Kudera, Tomas; Needham, Tersia; Mascellani, Anna; Kokoska, Ladislav (International journal of molecular sciences, 2024)
Diarrhoea remains an important public health concern, particularly in developing countries, and has become difficult to treat because of antibacterial resistance. The development of synergistic antimicrobial agents appears to be a promising alternative treatment against diarrhoeic infections. In this study, the combined effect of tetracycline together with either nitroxoline, sanguinarine, or zinc pyrithione (representing various classes of plant-based compounds) was evaluated in vitro against selected diarrhoeic bacteria (Enterococcus faecalis, Escherichia coli, Listeria monocytogenes, Shigella flexneri, Vibrio parahaemolyticus, and Yersinia enterocolitica). The chequerboard method in 96-well microtiter plates was used to determine the sum of the fractional inhibitory concentration indices (FICIs). Three independent experiments were performed per combination, each in triplicate. It was observed that the combination of tetracycline with either nitroxoline, sanguinarine, or zinc pyrithione produced synergistic effects against most of the pathogenic bacteria tested, with FICI values ranging from 0.086 to 0.5. Tetracycline-nitroxoline combinations produced the greatest synergistic action against S. flexneri at a FICI value of 0.086. The combinations of the agents tested in this study can thus be used for the development of new anti-diarrhoeic medications. However, studies focusing on their in vivo anti-diarrhoeic activity and safety are required before any consideration for utilization in human medicine.
Keywords: Microbial Sensitivity Tests; průjem; antibacterial resistance; Alkaloids; antimicrobial agents; Humans; alkaloidy; Nitroquinolines; Tetracycline; Drug Synergism; Diarrhea; mikrobiální testy citlivosti; lidé; antibakteriální látky; Organometallic Compounds; combination therapy; Pyridines; synergismus léků; organokovové sloučeniny; Anti-Bacterial Agents; synergistic effect; pathogens; pyridiny; tetracyklin; Bacteria; nitrochinoliny; diarrhoea